Jurisdição constitucional e soberania do povo - Marques, Antônio Silveira (2009)
The present work addresses the subject of the Constitutional Jurisdiction and People s Sovereignty and examines the apparent incompatibility between judicial review, namely review made by the Supreme Court in its current form, and the principle of the people s sovereignty, stressing the process of judicialization of politics . The author initially seeks to reconstruct the history of constitutionalism and judicial review in the 20th century, starting with the discussions of Hans Kelsen and Carl Schmitt about who had legitimacy to be the guardian of the German Reich s Constitution and examining the core points of these two thinkers. The second chapter reviews the discussions and conclusions of the first chapter and then begins a dialogue with the thoughts of contemporary authors such as Jürgen Habermas and Ronald Dworkin. These authors examined the growth of judicial functions, especially after Second World War, reaching conclusions on the necessity of imposing limits to judicial review in its current form. In the third and final chapter this question is addressed by examining the paradigmatic decision of the Brazilian Supreme Court concerning political party fidelity that created a new constitutional precedent by establishing a punitive norm an action not explicit in Article 55 of the Brazilian Constitution applicable to those considered unfaithful to their political parties. This research examines the limits of Brazilian rule of law, discussing the consequences of the unprecedented increase in judicial functions, especially by the Supreme Federal Tribunal, and the necessity of harmonizing governmental power in Brazil specifically, how to reconcile the current trend towards a stronger judiciary with the principle of the people s sovereignty, especially when laws pass through the control of the judiciary branch